Evaluation of tracheobronchial branching abnormalities in patients with microtia using chest computed tomography. (November 2017) - Li, Chuan; Jiang, Haiyue; Chen, Jingning; Wu, Rongwei; Bi, Ye; Yang, Meirong; Zhang, Ye; Pan, Bo
Abstract: Background: The objective of this study was to identify the characteristics and incidence of Tracheobronchial branching abnormalities in patients with microtia and to evaluate the risk of anesthesia. Methods: A total of 204 consecutive microtia patients and 465 nose cosmetic patients without microtia received a preoperative chest computed tomography. A retrospective study was performed with the clinical and imaging data from July 2016 to April 2017. Results: With the chest computed tomography images, a total of 7 cases were documented with Tracheobronchial branching abnormalities, including 6 cases among the microtia patients and 1 case among the cosmetic patients without microtia. The incidence of Tracheobronchial branching abnormalities was higher in microtia patients than the cosmetic patients without microtia (2.94% versus 0.22%, P < 0.01). Conclusions: The incidence of Tracheobronchial branching abnormalities was high in patients with microtia. Preoperative diagnosis of tracheal bronchus can help anesthesiologists avoid complications. Microtia with Tracheobronchial branching abnormalities may involve a new syndrome previously undiscovered or just another extension with the very wide spectrum of microtia.